Zika Virus and its Threads to Microcephaly - Dias Rima Sutiono; Cintya Pradnya Pratita (PT Kalbe Farma Tbk., 2018)
The infection of ZIKV is through transplacental transmission. Polymerase Chain Reaction (PCR) detected the strains of ZIKV inside amniotic fluid only when in other fluids : serum and urine, revealed negative results. Microcephaly with numerous calcifications were discovered in the fetus of all cases. Ventriculomegaly and CNS structures anomalies were also discovered, though some structures such as subcortical nuclei of the brain and ascending dorsal columns of the spinal tract were well preserved. Infeksi ZIKV melalui transmisi plasenta. Galur ZIKV dalam cairan ketuban dapat dideteksi menggunakan Polymerase Chain Reaction (PCR) hanya jika cairan lainnya, serum dan urin, negatif. Mikrosefali dengan kalsifikasi di semua kasus; lingkar kepala janin di bawah persentil kedua (34 cm). Ventrikulomegali dan struktur system saraf pusat abnormal, meskipun beberapa struktur seperti inti subkortikal otak dan jaras dorsalis medulla spinalis masih baik.